PATTERN OF SUBSTANCE USE DURING COVID-19 - Jat, Muhammad Ilyas; Arain, Muhammad Tarique; Washdev, Washdev; Das, Kheenpal; Qureshi, Saima; Bhatia, Moti Ram (Journal of Pakistan Psychiatric Society, 2023)
Objective: To assess the impacts of covid-19 on substance use behavior. Study Design: A descriptive cross-sectional study. Place and Duration: Department of Psychiatry, Dow Medical College, Dr. Ruth KM Pfau Civil Hospital, Karachi and Model Addiction Treatment and Rehabilitation Centre (MATRC) Anti Narcotic Force, Karachi from December 16th 2020 to 15th April 2021. Methodology: Male patients of substance use disorders visiting on out-patient bases were enrolled and their status of covid-19 was assessed and impact of covid-19 on their substance use behavior was recorded. Sample size was of 250 clients and non-probability consecutive type sampling was done. Ethical approval was sought before commencement of study. Results: The mean age of 250 participants was 28.2 +- 8.25 years. Out of total 24 (9.6%) were came out PCR positive as Covid-19 while 226 (90.4%) were negative for covid-19. When they were asked regarding the effect of covid-19 on their substance taking behavior, 138 (55.2%) were in the favor that this pandemic has increased their substance using habit while 112 (44.8%) replied that their substance using behavior has been remained as usual and covid-19 has not affected it. Statistically covid-19 status whether positive or negative was significantly related with type of substance use as well as mode of substance use having P value of less than 0.05. While the effect of covid-19 over the substance using behavior was also significantly associated having P value of less than 0.05. Conclusion: The impact of covid-19 on substance use behavior was quite high in terms of usage, amount and mode of taking substance.